Knowledge Hiding Behaviors and Team Creativity: The Contingent Role of Perceived Mastery Motivational Climate. (September 2019) - Bari, Muhammad Waseem; Abrar, Muhammad; Shaheen, Sadia; Bashir, Mohsin; Fanchen, Meng
The present study explains how different factors of knowledge hiding (e.g., evasive, playing dumb, and rationalized) influence on team creativity. Drawn on social exchange theory, the present study theorizes that factors of knowledge hiding have a negative relationship with team creativity, and absorptive capacity mediates this relationship. In addition, the perceived mastery motivational climate (PMMC) as a moderator attenuates the negative relationship between factors of knowledge hiding and team creativity. Study 1, an investigation (through the experience sampling method) from 41 participants of social media, confirms the existence of knowledge hiding practices in Pakistan. Study 2 applied a partial least squares, structural equation modeling approach on randomly selected time lag data of 282 respondents from state-owned universities of Pakistan. Results show that evasive hiding and playing dumb have a significant negative relationship with team creativity; however, rationalized hiding does not affect significantly on team creativity. The absorptive capacity also does not mediate the relationship between factors of knowledge hiding and team creativity. The PMMC attenuates the negative influence of evasive hiding and playing dumb on team creativity; however, the PMMC does not moderate the influence of rationalized hiding on team creativity. The implications and future research directions are discussed in the last section of this study.